Pengaruh Work-Life Balance, Disiplin Kerja, Lingkungan Kerja Fisik dan Stres Kerja Terhadap Kepuasan Kerja Pegawai Tempat Pelelangan Ikan I Dan II Tasikagung Rembang - Hazizatul Maula; Syaiko Rosyidi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Job satisfaction is one of the key factors influencing employee productivity and performance across various industrial sectors. This study aims to analyze the effects of work–life balance, work discipline, physical work environment, and job stress on the job satisfaction of employees at Fish Auction Places I and II Tasikagung, Rembang. The work–life balance variable consists of four dimensions: work interference with personal life, personal life interference with work, work–life enhancement, and personal life enhancement. This research employs a quantitative approach using a saturated sampling technique involving the entire population of 48 employees at Fish Auction Places I and II Tasikagung, Rembang. Data were collected through questionnaires that had passed reliability and validity tests. The results indicate that work interference with personal life and personal life interference with work have a significant negative effect on job satisfaction. Job stress has a negative but insignificant effect on job satisfaction, while work–life enhancement has a positive but insignificant effect. Meanwhile, personal life enhancement, work discipline, and the physical work environment have a significant positive effect on job satisfaction. The coefficient of determination shows a value of 0.615 or 61.5%, indicating that 38.5% of job satisfaction is explained by factors outside the research model.